Kesetaraaan Hak dalam Organisasi Paskibra SMA Sejahtera 1 Depok - Chealsea Khalisah Khalisah; Bunga Anindya Putri; Ahmad Warsito; Safa Putri Syabilla; Fina Sania Kaila Pontoh; Muhammad Nur Tirto Adji; Muhammad Rifandi; Mochdar Soleman (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This study examines the implementation of democratic principles in the decision-making process within the Paskibra organization at SMA Sejahtera 1 Depok. The research focuses on three main aspects: members' participation in organizational decision-making, the implementation of members' rights and responsibilities based on the concept of the social contract, and the challenges encountered in applying democratic values within the organization. A qualitative research method with a descriptive approach was employed. Data were obtained through interviews and direct observations involving the chairperson, vice-chairperson, and several active members selected using purposive sampling. The collected data were analyzed using the Miles and Huberman interactive model, which consists of data reduction, data presentation, and conclusion drawing. The results reveal that democratic principles have generally been practiced within the Paskibra organization through deliberation, group discussions, and voting mechanisms that encourage member involvement. The election of the organization’s chairperson and various decision-making processes were conducted openly, allowing members to express their opinions and contribute to organizational decisions. Nevertheless, several factors continue to hinder the effective implementation of democracy, including members' limited confidence in sharing their views, the influence of seniority, the tendency to follow the majority opinion, and communication barriers during discussions. Overall, democratic practices within the organization have been implemented reasonably well. However, greater efforts are still required to encourage more active participation from all members, thereby creating a more inclusive and effective decision-making process.